COLLECTION, STORAGE AND ANALYSIS OF WRITERS’ PERSONAL LIBRARIES - Prokopčik, Marija (Knygotyra, 2016)
COLLECTING, CURATING AND RESEARCHING WRITER’S LIBRARIES: A HANDBOOK. EDITED BY RICHARD W. ORAM AND JOSEPH NICHOLSON. LANHAM: ROWMAN & LITTLEFIELD, 2014. 218 P. ISBN 978-1-4422-3497-0.